2013
DOI: 10.1073/pnas.1302426110
|View full text |Cite
|
Sign up to set email alerts
|

Microbial diversity in The Cedars, an ultrabasic, ultrareducing, and low salinity serpentinizing ecosystem

Abstract: The Cedars, in coastal northern California, is an active site of peridotite serpentinization. The spring waters that emerge from this system feature very high pH, low redox potential, and low ionic concentrations, making it an exceptionally challenging environment for life. We report a multiyear, culture-independent geomicrobiological study of three springs at The Cedars that differ with respect to the nature of the groundwater feeding them. Within each spring, both geochemical properties and microbial diversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
204
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 111 publications
(227 citation statements)
references
References 37 publications
9
204
3
Order By: Relevance
“…While the shallow groundwater communities were similar to those described in other terrestrial serpentinizing sites, the deep groundwater microbial community was distinctly different from any other previously described terrestrial serpentinizing community16. The shallow groundwater-fed springs were numerically dominated by microbes related to the genus Hydrogenophaga within Betaproteobacteria 16. Furthermore, alkaline fluid from other terrestrial serpentine-hosted ecosystems also contained abundant Hydrogenophaga -related microbes17181920.…”
mentioning
confidence: 47%
“…While the shallow groundwater communities were similar to those described in other terrestrial serpentinizing sites, the deep groundwater microbial community was distinctly different from any other previously described terrestrial serpentinizing community16. The shallow groundwater-fed springs were numerically dominated by microbes related to the genus Hydrogenophaga within Betaproteobacteria 16. Furthermore, alkaline fluid from other terrestrial serpentine-hosted ecosystems also contained abundant Hydrogenophaga -related microbes17181920.…”
mentioning
confidence: 47%
“…Fluids with relatively recent recharge from the surface (on a scale of tens of thousands of years) lie along the GMWL, reflecting their meteoric origin (Craig, 1961). In contrast, saline waters and brines that have been sequestered in the deep crystalline rocks of the Precambrian Shields worldwide have been shown to have δ 18 O and δ 2 H signatures well elevated over those of the GMWL A similar pattern of community composition based on fluid origins has also been reported in the Fennoscandian Shield (Itävaara et al, 2011), a terrestrial serpentinite system in northern California (the Cedars) (Suzuki et al, 2013), the Tablelands Ophiolite and other serpentinizing sites . In the Fennoscandian Shield, the microbial communities inhabiting 100-m increments of the Outokumpu deep borehole (up to1500 m depth) were reported.…”
Section: Deep Subsurface Metabolism C Magnabosco Et Almentioning
confidence: 63%
“…There, Proteobacteria dominated the oxygenated, shallow (0-900 m) samples, whereas Firmicutes dominated the deeper samples (900-1000 m, 1400-1500 m) of the borehole (Itävaara et al, 2011). In the case of terrestrial serpentinites Schrenk et al, 2013;Suzuki et al, 2013), it has been reported that Firmicutes (and Chloroflexi in the case of Suzuki et al (2013)) dominate serpentinite springs fed solely by deep groundwater, whereas the sites whose water was a mixture of deep and shallow groundwater contain communities dominated by Betaproteobacteria. In the shallow sites, it is expected that the Betaproteobacteria such as Hydrogenophaga make use of the abundant O 2 and H 2 associated with the paleometeoric waters, whereas the Firmicutes-dominated sites are characterized by organisms capable of dealing with the low abundance of oxidants and/or with the ability to switch between autotrophic and mixtrotrophic growth .…”
Section: Deep Subsurface Metabolism C Magnabosco Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of H 2 and CH 4 , the latter formed through abiotic reduction of CO 2 [Proskurowski et al, 2008;Lang et al, 2012], are major energy sources for microbial activity and have been shown to support prolific microbial communities in peridotite-hosted hydrothermal systems [Kelley et al, 2005;Brazelton et al, 2006Brazelton et al, , 2012Suzuki et al, 2013;Brazelton et al, 2013]. Additionally, serpentinization of ultramafic rocks generally produces hyperalkaline fluids (pH > 10) with high Ca…”
mentioning
confidence: 99%